Foreign direct investment in land in West Africa: The status quo, lessons from other regions, implications for research - Wouterse, Fleur Stephanie; Deininger, Klaus; Selod, Harris; Badiane, Ousmane; Swinnen, Johan; von Braun, Joachim; Zilberman, David (International Food Policy Research Institute, 2011)
The long-term imbalances between supply and demand and international trade changes that triggered the recent crises in global food markets are also fueling a spike in overseas investments in agricultural land. Africa is a major destination of investment flows because it has the largest reserves of arable land.